Consumer Engagement in the Era of Social Media: Literature Review About Recent Interactions, Influence and Measurement - Erni Widiastuti (International Journal of Business and Quality Research, 2023)
Social media has become one of the main platforms for consumers to interact with brands and products. Consumer engagement in social media has become an increasingly important research topic in understanding how these interactions influence consumer behavior and business performance. This research aims to present a review of the current literature on consumer engagement in the social media era, focusing on aspects such as interaction, influence, and measurement. This literature review describes recent developments in the understanding of interactions between consumers and brands on social media, and their impact on purchasing decisions and consumer loyalty. In addition, this research also reviews innovative and current measurement methods used to measure consumer engagement on social media platforms. Through comprehensive literature analysis, this research identifies key trends and findings in consumer engagement in the social media era, providing valuable insights for marketing practitioners and researchers to develop better strategies. Effective in utilizing the potential of social media to interact with consumers. This research also highlights the need for further research to delve deeper into the dynamics of consumer engagement in the changing social media context.